Bibliometric Analysis: Rewards using the Scopus Database - Ramadhina, Aisya Safira; Asfiah, Nurul; Nurhasanah, Siti; Umami, Riza (International research journal of management, IT and social sciences, 2024)
This research explores the role of rewards in improving employee performance and related aspects. Bibliometric analysis was conducted using the Scopus database from 2013 to 2023 to evaluate the effect of rewards on performance. The literature review identifies types of rewards, both material (salary, bonus) and non-material (verbal recognition, organizational commitment). The results provide in-depth insight into reward dynamics with practical implications for human capital management and a basis for further research. The focus of article publication on Scopus has fluctuated, with a peak in 2019, a decline in 2020-2021, and a surge in 2022-2023. Research findings include the positive effect of extrinsic rewards on intrinsic motivation, variations in satisfaction relationships to employee rewards and moving intentions, and the positive impact of organizational characteristics on the adoption of open innovation. Journal publication graphs show trends in Scopus, with Compensation And Benefits Review and Human Resource Management International Digest leading the way with 7 articles. Cluster analysis using VOSviewer identified 38 reward-related topics, including "reward system", "reward function", and "performance".